(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
In this article, future engineers’ opportunities for learning 3D modelling, programming 2D/3D modelling through computers, and the introducing design technologies using BIM technologies will be reviewed. The given materials may be intriguing for technological university professors whose jobs are related to engineering as well.